Description of Bukhara Khanate in the Diaries of Tourist Antonio Jenkinson - Rakhmanovich, Turaev Shukhrat; o’g’li, Choriyev Jasur Beknazar (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This article analyzes the data collected by the ambassadors as a result of his travels to the Khanate, his diaries, archival sources of different periods, sources of scientific literature were sent from Russian Empire to Central Asia.